A história da literatura brasileira, de Sílvio Romero, como lugar de memória - Gilvaneide de Sousa Santos (2015)
This research analyses the place occupied by the book História da Literatura Brasileiraby Sílvio Romero in the historiographic studies to understand its position in the contexts of 19th Century. Problematizing this, its our goal to show possible readings to rearrange this book to the contemporary historicity establishment, because, according to Charles Baudelaire (1988) its necessary to think the past in the name of present. Saying that, we used concepts of sites of memory (lieux des mémoire) proposed by Pierre Nora (1981); document/monument, by Jacques Le Goff (2013); the conception of Modernity by Baudelaire (1988); the Presentism, by Hartog (2013); the concept of History, by Benjamin (2012) and the concept of Cultural Memory, by Jan Assmann (2008). We verified that the book História da Literatura Brasileira itis one of the foundation texts of our Brazilian Cultural Memory. It is alsorelated to our concept of Literature and to the Brazilian people because it is part of the national project of 19thCentury: to build an image unato the Nation state. To understand how the ethnographic approach of studying the Brazilian literature according to Sílvio Romero was developed, we used some interpretation of his work, such as Antonio Cândido with O Método crítico de Sílvio Romero (1963) and Sílvio Romero: teoria, crítica e história literária (1978).